Large scale three-dimensional modelling for wave and tidal energy resource and environmental impact: Methodologies for quantifying acceptable thresholds for sustainable exploitation. (1st October 2017) - Gallego, A.; Side, J.; Baston, S.; Waldman, S.; Bell, M.; James, M.; Davies, I.; O'Hara Murray, R.; Heath, M.; Sabatino, A.; McKee, D.; McCaig, C.; et al.
Highlights: We describe a modelling project to estimate the potential effects of wave & tidal stream renewables on the marine environment. Realistic generic devices to be used by those without access to the technical details available to developers are described. Results show largely local sea bed effects at the level of the currently proposed renewables developments in our study area. Large scale 3D modelling is critical to quantify the direct, indirect and cumulative effects of renewable energy extraction. This is critical to comply with planning & environmental impact assessment regulations and achieve Good Environmental Status.